Cognition, Economic Decision-Making, and Physiological Response to Indoor Carbon Dioxide: Does It Really Matter? - Stefan Flagner; Thomas Meissner; Steffen Künn; Piet Eichholtz; Nils Kok; Rick Kramer; Wouter van Marken-Lichtenbelt; Cynthia Ly; Guy Plasqui (Institute of Labor Economics (IZA), 2024)
This study provides novel evidence on the isolated effect of carbon dioxide on cognition, economic decision-making, and the physiological response in healthy office workers. The experiment took place in an air-tight respiration chamber fully controlling the environmental conditions. In a single-blind, within-subject study design, 20 healthy participants were exposed to carbon dioxide concentrations of 3,000 ppm and 900 ppm in randomized order, with each exposure lasting for 8 hours. We do not find evidence on a statistically significant effect on either cognitive or physiological outcome variables. Thus, the evidence shows that the human body appears to be able to deal with exposure to indoor carbon dioxide concentration of 3,000 ppm without suffering significant cognitive decline, changes in decision-making or showing any physiological response.
Keywords: D87; J24; Q54; 330; carbon dioxide; indoor air quality; cognition; economic decision-making; physiological response